Efficacy of zinc lactate and Lactobacillus bulgaricus on nutrition and health of broiler chickens - Parra Ferrín , Dayana; Cusme Lucas , Guido; Talledo Solórzano , Viviana; Loor Gorozabel , Braulio; Pazmiño Castro, Anderson; Cuenca-Nevárez, Gerardo José (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2023)
This investigation examined the effects of zinc lactate and Lactobacillus bulgaricus supplementation on the gastrointestinal microbiota of broiler chickens, analysing zootechnical, allometric, microbiological parameters and small intestine morphology. A total of 300 broiler chickens with an average initial weight of 47 g were distributed in four treatments in a completely randomised design. Treatments consisted of different zinc lactate and probiotic amounts added to the base diet. Chickens receiving the basal diet with organic zinc and L. bulgaricus showed a healthy response, remaining free of infectious agents for the 42-day study period. Treatment T1, with 30 mg of zinc lactate and 10 mg of probiotics per kg, showed improvements in weight gain, feed conversion, allometry, and intestinal health, as well as a healthy presence of gastrointestinal microbiota. Thus, the incorporation of zinc lactate (organic Zn) and probiotics based on L. bulgaricus into the basal diet of broiler chickens is an effective strategy to improve sanitary conditions and organic production of these species. Highlights: From: Efficacy of zinc lactate and Lactobacillus bulgaricus on nutrition and health of broiler chickens. Innovative Supplementation Strategy: This study presents an innovative approach by combining zinc lactate and Lactobacillus bulgaricus in broiler chickens’ diet, showcasing a novel method to enhance poultry health and organic production. Comprehensive Analysis of Gut Microbiota: The research provides a detailed analysis of the gastrointestinal microbiota, demonstrating how zinc lactate and Lactobacillus bulgaricus supplementation positively alters the gut environment in broiler chickens. Significant Improvements in Zootechnical Parameters: The study highlights notable improvements in zootechnical parameters, including weight gain and feed conversion ratios, underlining the efficacy of the supplementation strategy. Enhanced Intestinal Morphology: Examination of the small intestine morphology revealed significant health benefits, attributing these improvements to the synergistic effect of organic zinc and probiotic supplementation. Pathogen-Free Development over 42 Days: A key finding is the maintenance of a healthy, pathogen-free state in chickens throughout the 42-day study period, emphasizing the potential of this supplementation in promoting disease resistance in poultry farming.